The words we can't hear: decoding the language of objects through the eyes of object-oriented ontology - Dong Saul, Samuel Omar, author; Frazier, Jason, advisor; Dineen, Mark, committee member; Kissell, Kevin, committee member; Gravdahl, John, committee member (Colorado State University. Libraries, 2020)
The work presented in this paper investigates the presumption that objects relating to humans are part of a more significant philosophical discussion. Using the philosophical framework of Graham Harman's Object-Oriented Ontology (OOO) as the theoretical foundation, the thesis explores the acknowledgment that by not thinking about the sum of the material parts of objects and the cultural meanings of their interpretations, one could experience new relationships with his/her surrounding objects. Discussions on post-structuralist language theories in contemporary art address how artists use language and cultural symbols in art-objects, challenging already established cultural meanings. In addition, psychological theories of personification of objects, and how they help understand the life of non-living things, support the idea that objects communicate in non-verbal ways to other objects in their environment without the full awareness of people. Conclusively, the thesis will attempt to translate and interpret the unique relationship of living and non-living objects; how non-verbal code is left behind and by challenging language conventions, one can experience a new relationship with objects outside the cultural norms.
Keywords: language; personification of objects; visual communication; object-oriented ontology; contemporary art; philosophy of art